Oxidative stress in chronic lymphocytic leukemia: still a matter of debate. Issue 4 (21st March 2019) - D'Arena, Giovanni; Seneca, Elisa; Migliaccio, Ilaria; De Feo, Vincenzo; Giudice, Aldo; La Rocca, Francesco; Capunzo, Mario; Calapai, Gioacchino; Festa, Agostino; Caraglia, Michele; Musto, Pellegrino; Iorio, Eugenio Luigi; et al.
Abstract: There is a large body of evidence showing a strong correlation between carcinogenesis of several types of human tumors, including chronic lymphocytic leukemia (CLL), and oxidative stress (OS). The mechanisms by which OS may promote cancer pathogenesis have not been completely deciphered yet and, in CLL, as in other neoplasms, whether OS is a primary cause or simply a downstream effect of the disease is still an open question. It has been demonstrated that, in CLL, OS concomitantly results from increased reactive oxygen species (ROS) production, mainly ascribable to CLL cells mitochondrial activity, and impaired antioxidant defenses. Interestingly, OS evaluation in CLL patients, at diagnosis, seems to have a prognostic significance, thus getting new insights in the biological comprehension of the disease with potential therapeutic implications.